PLANNING OF DATA CONTENT ON BASIS OF STATISTICAL PARAMETER EVALUATION THEORY - G. S. Ravich (Наука и техника)
The paper considers a problem concerning improvement of a methodology for justification of data content while preparing management solutions in the cases when data expenses are relatively high. Such notion as «data value» is applied for the solution of a problem within the framework of  statistical parameter evaluation theory. The problem is solved from general positions and due to this such notion as «solution preparation» is applied in the paper.